Multiperspective simulations for implementing a change in service: stroke telethrombolysis. (4th June 2021) - Brown, Craig William; Elofuke, Petrus
Abstract : Simulation-based training has been used in a variety of ways to demonstrate and improve process elements of patient care. One example of this is in improving door-to-needle times in hyperacute stroke care. Changes in service by one team which affect another bring difference of opinions between service providers involved and can lead to interdepartmental conflict. In this report, we use Kurt Lewin's model for change to describe how a series of multiperspective simulation-based exercises were used in implementing a change in practice with the introduction of telethrombolysis within a large tertiary stroke referral hospital. The use of multiperspective or bidirectional simulation allowed a 'meeting of minds' with each service able to illustrate key themes to the other service. This was demonstrated through a series of simulation-based exercises. Following successful simulation-based exercises and subsequent interdepartmental agreement, a telethrombolysis pilot has been conducted within our centre. Ongoing audit of practice continues as this method of treatment delivery is continued. Further simulation work is planned as a national thrombectomy service is instigated.